Pergerakan Ulama dan Santri Dalam Perang Mempertahankan Kemerdekaan di Ambarawa 1945 - Ahmad Hidayatullah; Miftahul Khoiri (Tanjak: Sejarah dan Peradaban Islam, 2022)
The Proclamation of Indonesian Independence on August 17, 1945, is the fruit of a long struggle that has been achieved by the entire Indonesian nation. Everyone who has fought for their independence is still struggling to defend their independence from the Westerners who have re-occupied Indonesia. He has proven the task carried out in defending Indonesia's independence from the ulama and santri circles. This study reveals the movement of ulama and santri in the Battle of Ambarawa in 1945. Ulama who incidentally are religious leaders in this study are also described as war leaders who play a role in moving students or their followers. This research is a historical study, in historical research there are methods, namely: Heuristics are the stages of finding or collecting sources, verifying or criticizing sources, interpreting or interpreting, and historiography or historical writing. The results of this study state that: The Battle of Ambarawa was a series of battles from Semarang and Magelang. Resistance in this battle has involved ulama and santri in various areas around Ambarawa. Crowds of ulama, and santri, cooperated against the Allied alliance. The determination and fighting spirit has flared in the warrior's chest. Ceasefires such as bomb explosions, the fall of torpedoes, cannon fire from tanks, and warplanes colored the course of the battle. The Muslims in this case have made a large contribution in the form of a number of troops, so that the Battle of Ambarawa was won by the Republicans.